(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
This research article examines the problems of ensuring sustainable development goals (SDGs) in Uzbekistan. Uzbekistan is a landlocked country in Central Asia that faces numerous challenges to achieve sustainable development due to its rapidly growing population, limited natural resources, and insufficient infrastructure. The article analyzes the progress and challenges of Uzbekistan in achieving the SDGs and provides recommendations for policymakers to overcome the obstacles in achieving sustainable development.